Informe de avance del proyecto de investigación del comportamiento dinámico de estructuras de puentes - Agüero Barrantes, Pablo (2015)
This report presents the progress of the project formally proposed in the REPORT LM-PI-UP-04-2013 "Acquisition of shaking tables for teaching and research on the dynamic behavior of bridge structures". The work done to date on research and technology transfer through teaching and training focused on the theme of dynamic behavior of bridge structures is summarized.